SUBSTANTIATION OF THE NEED TO ESTABLISH THE READINESS OF FUTURE PSYCHOLOGISTS TO TACKLE CONFLICT SITUATIONS IN THE PROFESSIONAL ACTIVITY - Анатолій ЮРКОВ (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2021)
The article studies the theoretical review and substantiation of psychological and pedagogical aspects of the problem of establishment of the readiness of future military psychologists to tackle conflict situations in their professional activities. The conducted scientific research made it possible to reveal the main loads and specifics of the practical activities of future military psychologists during their service in military units, which, in turn, actualized the need to establish readiness among young officers even at the stages of training in higher military educational institutions. The paper analyzes the issue of "readiness for professional activity", and shows that the space of scientific thoughts is heterogeneous and has many approaches to understanding this definition. It is identified that readiness for the future military psychologist to tackle conflict situations in professional activity is a complex characteristic of the individual, including a system of professional motives, psychological qualities, attitudes and states, subject and intellectual knowledge, skills and abilities, which together is the key to the effective performance of functional duties. The paper proposes to interpret the process "readiness of future military psychologists to resolve conflict situations in their professional activities" as a holistic training covering professional knowledge, skills, patriotic views and beliefs; professional orientation to military service; reflection of their achievements; professional self-improvement. It is found that the content of the readiness of future military psychologists to tackle conflict situations in professional activity is a set of relevant knowledge and skills, which is provided by mastering the relevant profession (professional training), acquiring professionally important personality qualities, entering professional activity after graduation from a higher military educational institution (professional adaptation) skill development in military service (professional self-improvement). Based on the best practices of the scientific community, five main components of readiness are outlined: motivational, value-oriented, communicative-informational, creative, operational-activity.